PERAN PENDIDIKAN KEWARGANEGARAAN DALAM MENINGKATKAN ETIKA ANAK DI SEKOLAH DASAR - Maisy Julia Syahira; Aulia Suci Nabilla; Rohmadhan, Alfiandi; Ari Suriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Civic Education (PKn) plays a crucial role in shaping character and enhancing children's ethics in elementary schools. This study aims to analyze how PKn learning can help students understand moral values and apply them in their daily lives. The research method used is a literature study by analyzing various relevant scientific sources. The findings indicate that active learning methods such as group discussions, case studies, simulations, and role-playing are effective in increasing students' ethical awareness. Furthermore, the teacher's role as a role model significantly influences children's moral attitudes. PKn not only improves students' politeness and discipline at school but also positively impacts their behavior at home. By gaining a deeper understanding of ethical concepts, students become more responsible, empathetic, and honest in their social lives. This study contributes to the field of education by highlighting the importance of an interactive approach in PKn teaching to shape children's character. However, the limitation of this study lies in its scope, which is restricted to a few literature sources.